The enhancement of power quality for the distribution system via dynamic voltage restorer - Ali Basim Mohammed; Mohd Aifaa Mohd Ariff (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper represents a new configuration of the dynamic voltage restorer consists of approximate classical sliding mode differentiator (ACSMD) with the terminal sliding mode controller (TSMC) as the nonlinear sliding variable. In this study, the proposed structure of the DVR is utilized to maintain the magnitude of the load voltage at a constant value, maintain the system total harmonic distortion (THD), boost the robustness property and minimize the steady-state error. The power quality has received more interest due to the implementation of various industrial devices and critical loads at the distribution side. Nowadays, the main challenges in power quality in the system are voltage sags/swells, harmonics and voltage imbalance. Various devices are utilized to address these challenges. The dynamic voltage restorer is one of these devices. It is connected in series with the distribution system and injects a proper voltage magnitude to maintain the voltage load at the constant value. In this paper, the DVR model with the ASMF and TSMC is implemented in using MATLAB/Simulink. The proposed controller is evaluated using the standard voltage sag indices.